A comparison of turbine entrainment rates and seasonal entrainment vulnerability of two sympatric char species, bull trout and lake trout, in a hydropower reservoir. (30th March 2020) - Harrison, Philip M.; Ward, Taylor; Algera, Dirk A.; Culling, Brad; Euchner, Ted; Leake, Alf; Crossman, James A.; Cooke, Steven J.; Power, Michael
Abstract: Potadromous salmonids that reside in hydropower reservoirs often have a high recreational and conservation value. However, the potential seasonal turbine entrainment vulnerability patterns of potadromous salmonids are not well understood. Here, we use acoustic telemetry to test the hypothesis that adults of two species of the Salvelinus genus (bull trout and lake trout) differ in their seasonal patterns of entrainment and entrainment vulnerability over a 2‐year period. Our results show that while both species were entrained at similarly low annual rates (~1%), these two salmonids differed in their patterns of forebay residency and proximity, with implications for entrainment risk. Bull trout occupied the forebay at low rates across all seasons, with no clear seasonal pattern of forebay proximity. In contrast, lake trout displayed a strongly seasonal pattern of entrainment vulnerability with a distinct movement away from the forebay during the summer, and a large increase in forebay proximity and use in the winter and spring. These findings provide a novel species‐specific demonstration of the potential entrainment vulnerability of lake trout. The seasonal patterns of entrainment vulnerability seen in previous bull trout studies, where bull trout occupied top pelagic predator niches, were not replicated in our study where bull trout occur in sympatry with another top pelagic predator. These findings, which indicate that species composition plays an important role determining entrainment vulnerability, have important implications for the conservation of indigenous lake trout and bull trout populations, and together highlight the need for a site‐specific approach to entrainment quantification.